2006
DOI: 10.1080/00016340600566121
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between psychosocial profile, health practices, and pregnancy outcomes

Abstract: Thin women with a poor psychosocial profile and who are depressed during pregnancy are at increased risk of giving birth to low birth weight and preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 29 publications
4
118
1
13
Order By: Relevance
“…Other studies have also showed that pregnant women suffer from varying degrees of depression and from anxiety disorders (31,32). It seems unknown fear, stress, and daily activities pressure make them feel more to receive such information.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also showed that pregnant women suffer from varying degrees of depression and from anxiety disorders (31,32). It seems unknown fear, stress, and daily activities pressure make them feel more to receive such information.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal BMI is an important risk factor for preterm birth and is of public health importance independently. Some researchers have shown an increase in preterm birth with low BMI or BMI <18.5 kg/m 2 [19][20][21]. Others support an increase in provider initiated preterm birth with increasing BMI [22,23].…”
Section: Preterm Births and Gestational Age At Birthmentioning
confidence: 99%
“…O estresse na gestação está associado à ocorrência de abortos espontâneos (GREENBERG, 2002;MULDER et al, 2002), ao trabalho de parto prematuro (STEER, 2005;MULDER et al, 2002), à hipertensão arterial induzida pela gravidez (BJELICA, 2004;TAKIUTI e KAHHALE, 2001), ao baixo peso ao nascer (LECH;MARTINS, 2003;MULDER et al, 2002;NEGGERS et al, 2006), podendo afetar também o desenvolvimento do feto (RIEGER et al, 2004; R. da Educação Física/UEM Maringá, v. 20, n. 1, p. 121-129, 1. trim. 2009 MULDER et al, 2002).…”
Section: Introductionunclassified